Pengaruh Audit Internal dan Kepemimpinan Beretika Terhadap Implementasi Good Corporate Governance Serta Dampaknya pada Kinerja Perusahaan - Novatiani, Ait; Rachmawati, Rima; Octavia, Evi; Komara, Acep (Universitas Swadaya Gunung Jati, 2024)
The performance of BUMNs is not optimal because there are still many BUMNs that experience losses. Company performance has long been a source of discussion. Thus, the purpose of this research is to analyse the relationship between internal audit, ethical leadership and the implementation of good corporate governance in improving company performance. The population of this study were 36 BUMNs in Indonesia, with a sample size of 182 respondents, selected using saturated/census sampling techniques. Data were obtained by online surveys through google forms and direct visits to several BUMNs, then analysed using SEM-PLS. The type of question used in this research is a closed question. The results prove that internal audit affects the implementation of good corporate governance and company performance. Ethical leadership affects the implementation of good corporate governance and company performance. Furthermore, the research results prove that the implementation of good corporate governance has an influence on company performance. This research can contribute to BUMNs in Indonesia, especially in improving the performance of their companies, increasing the trust of investors, stakeholders, and society in general to BUMNs.